Avaliação de usabilidade em sistema de iluminação pública : análise com usuários e propostas de melhoria - Donato , Mateus (2025)
With the digitalization of public administration, computerized systems have become essential for municipal management, supporting decision-making, resource control, and service delivery. However, their effectiveness depends on intuitive and accessible interfaces. This article evaluates the interface of a public lighting system, identifying flaws and proposing improvements. Remote user testing was conducted with real users, including interaction analysis and the application of the System Usability Scale (SUS). The average SUS score was 68.75, indicating minimally satisfactory usability. The results provide support for improving the user experience in future versions of the system.